A Birds Eye View on Different Ayurvedic Treatment Modalities in Cerebral Palsy in Children - Sharma, Narinder; Gupta, Aman; Khajuria, Dheeraj (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Cerebral palsy (CP) is a permanent, non-progressive, and occasionally evolving disorder of tone, movement, or posture caused by a change to the developing brain, which may be due to birth asphyxia, trauma, infection, or prematurity in antenatal, perinatal, or post-natal periods. Material and Methods: A systematic review of the literature available was carried out on PubMed, Ayush Research Portal, Dhara, and Scopus regarding Ayurvedic intervention in the management of CP. Results: The treatment program for a child with spasticity may include Ayurvedic drugs, allied health therapy, and exercise. Ayurveda recommends multiple treatment options for CP. Out of these treatment options herbal drugs, Panchakarma therapies, etc. are most commended for this disease. Discussion: The present paper reviewed various clinical studies to ascertain the efficacies of these modalities and found that Ayurveda can efficiently manage CP along with its associated condition by improving movement, reducing spasticity, and strengthening the muscles. Conclusion: The current review provides motivating evidence for the usage of herbal treatment in CP and further research utilizes robust available methodology. Cerebral palsy (CP) is a motor function disorder caused by a defect in the developing brain, which may be due to birth asphyxia, trauma, infection, or prematurity in antenatal, perinatal, or postnatal periods. In developing nations like India, the incidence of CP is approximately 3/1,000 live births. This has not altered recently despite better antenatal care and public health.[1] Although CP begins in childhood, it impacts the individual’s whole life course as well as the health-care system. Identifying appropriate interventions to alleviate disability throughout the life of a person with CP is urgent.[2] The male gender was classified as a risk factor for CP. Epilepsy has been shown to be the most commonly associated comorbidity.[3] CP is predominantly a mobility issue, but many children who have it also have additional